EDUCATIONAL INNOVATION EXPRESSION IN COMMUNITY - Leliugiene, Irena; Simonaitytė, Ieva; Kaušylienė, Angelė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
In the article solves the following problematic issue: 1.What educational tools occur in the educational innovation community? The aim of article is to base the resolution of the educational innovations theoretically and empirically. The object of the researches resolution of the educational innovation. General research results. Performed the data analysis suggests that the surveyed communities are sufficiently concentrated, and members of the activity level is high enough, focus and activity is sufficient. As well as in communities dominated by positive approach to training and education, the absolute majority of respondents are motivated to learn and improve. An analysis chairman of community operational assessments showed that most community leader applies novation to develop an innovative learning environment in the planning and allocation of resources as well as finding new opportunities for business development and community members in education